The detection of Schistosoma bovis in livestock on Pemba Island, Zanzibar: A preliminary study - Tom Pennance (Elsevier, 2021)
Schistosoma bovis is a parasitic trematode of ungulates transmitted by freshwater snails in Sub-Saharan Africa causing bovine intestinal schistosomiasis that leads to chronic morbidity and significant agricultural economic losses. The recently reported occurrence of Bulinus globosus infected with S. bovis for the first time on Pemba Island (Zanzibar, United Republic of Tanzania) is a cause of concern for livestock/wildlife health and complicates the surveillance of Schistosoma haematobium. To confirm that local cattle are infected with S. bovis, fresh faecal samples were collected from six adult cows surrounding two schistosomiasis transmission sites in Kinyasini, Pemba Island. Schistosome eggs were concentrated, egg hatching stimulated and miracidia were individually captured and identified by analysis of the partial mitochondrial cytochrome c oxidase subunit 1 (cox1) and the partial nuclear internal transcribed spacer region (ITS1+5.8S+ITS2). Two S. bovis miracidia were collected from one faecal sample with two cox1 haplotypes, one matching cox1 data obtained from S. bovis cercariae, collected previously at the same site in Pemba, the other matching S. bovis cox1 data originating from coastal Tanzania. The findings conclude that S. bovis transmission has been established on Pemba Island and is likely to have been imported through livestock trade with East Africa. Increasing the sensitivity of non-invasive diagnostics for bovine schistosomiasis, together with wider sampling, will enable a better assessment on the epidemiology of S. bovis on Pemba Island.